Innovative Behavior And Organizational Commitment To Mediate The Influence Of Organizational Culture On Job Performance - Mirhamida Rahmah; Dinda Fatmah; Lukman Hakim; Syaiful Hasani; Yusriyah Rahmah; Zakiyah Zulfa Rahmah (Universitas Pendidikan Indonesia, 2022)
In this era of uncertainty and environmental change accompanied by an increasingly fierce level of competition, it is very necessary for human resources who have innovative behavior so that an organization can survive. Organizational progress will also be achieved if human resources have good performance. The reason for this study was to clarify the job of innovative behavior and organizational commitment to intercede the impact of organizational culture on job performance. Populace of this study are graphic design employee of Offset Printing Companies (OPC) in East Java. The sample utilized upwards of 160 individuals with the cluster sampling technique. The analytical procedure used is Path Analysis using the SmartPLS version 3. The aftereffects of this study are relied upon to assist future exploration in focusing on the elements that with canning influence the exhibition of visual computerization representatives. The consequences of this study are likewise expected to add new information that will enhance the hypothesis of human asset the board and organizational behavior theory, especially those related to the job performance of employees of OPC.Di era ketidakpastian dan perubahan lingkungan yang disertai dengan tingkat persaingan yang semakin ketat, sangat diperlukan sumber daya manusia yang memiliki perilaku inovatif agar suatu organisasi dapat bertahan. Kemajuan organisasi juga akan tercapai jika sumber daya manusia memiliki kinerja yang baik. Penelitian ini bertujuan untuk mengetahui pekerjaan perilaku inovatif dan komitmen organisasi dapat memediasi pengaruh budaya organisasi terhadap kinerja karyawan. Populasi dalam penelitian ini adalah karyawan desain grafis Percetakan Offset di Jawa Timur. Sampel yang digunakan sebanyak 160 orang dengan teknik cluster sampling. Prosedur analisis yang digunakan adalah analisis jalur menggunakan SmartPLS versi 3. Penelitian ini diharapkan dapat menambah informasi baru yang akan memperkuat hipotesis perilaku inovatif dan komitmen organisasi dalam memediasi pengaruh budaya organisasi terhadap kinerja karyawan, terutama yang berkaitan dengan kinerja karyawan OPC